Barriers to patient and family‐centred care in adult intensive care units: A systematic review - Frank Kiwanuka; Shah Jahan Shayan; Agbele Alaba Tolulope (Wiley, 2019)
Abstract Aim Despite remarkable theoretical evidence of positive outcomes of patient and family‐centred care, it is rarely performed in the intensive care setting. The aim of this review was to assess the barriers to patient and family‐centred care among healthcare providers, patients and family members in adult intensive care units. Design A systematic review of both qualitative and quantitative studies. Methods The search strategy sought for published peer‐reviewed research papers limited to English language from conception to 2018. The review protocol was registered in the CRD Prospero database (CRD42018086838). Literature search was carried out in four databases: EMBASE, Cochrane Library, PubMed and Scopus where keywords "barriers," "patient and family centered care," "patient‐centered care" and "intensive care unit" appeared in any part of the reference. Hand search of reference lists of identified papers was also done to capture all pertinent materials. Each study was assessed by three independent reviewers against the inclusion criteria. Evidence was graded according to sampling quality, quantity and measurement of intended outcomes. Screening of studies and citations resulted in seven studies that were included in the analysis. Results Barriers to patient and family‐centred care broadly fall under four categories; lack of understanding of what is needed to achieve patient and family‐centred care, organizational barriers, individual barriers and interdisciplinary barriers.